Impact of Comorbid Alcohol Use Disorder on Health-Related Quality of Life Among Patients With Depressive Symptoms - Luoto, Kaisa E.; Lindholm, Lars H.; Koivukangas, Antti; Lassila, Antero; Sintonen, Harri; Leinonen, Esa; Kampman, Olli (Frontiers in Psychiatry, 2021)
Background and aim In psychiatric clinical practice, comorbidity of depression and alcohol use disorder (AUD) is common. Both disorders have a negative impact on health-related quality of life (HRQoL) in general population. However, research on the impact of comorbid AUD on HRQoL among clinically depressed patients is limited. The purpose of this study was to explore the impact of a psychosocial treatment intervention on HRQoL for depressive patients in specialized psychiatric care with a special focus on the impact of AUD on HRQoL. Material and Methods Subjects were 242 patients of the Ostrobothnia Depression Study (ClinicalTrials.gov Identifier NCT02520271). Patients referred to specialized psychiatric care who scored at least 17 points on the Beck Depression Inventory at baseline and who had no psychotic disorders were included in the ODS. The treatment intervention in ODS comprised behavioral activation for all but began with motivational interviewing for those with AUD. HRQoL was assessed regularly during 24-month follow-up by the 15D instrument. In the present study, HRQoL of ODS patients with or without AUD was compared and the factors explaining 15D score analyzed with a linear mixed model. In order to specify the impact of clinical depression on HRQoL during the early phase of treatment intervention, a general population sample of the Finnish Health 2011 Survey was used as an additional reference group. Results HRQoL improved among all ODS study sample patients regardless of comorbid AUD during the first year of follow-up. During 12 to 24 months of follow-up the difference between groups was seen as HRQoL continued to improve only among the non-AUD patients. A combination of male gender, anxiety disorder, and AUD was associated with the poorest HRQoL in this sample. In combined sample analyses with the reference group, clinical depression had an impact on HRQoL in short-term follow-up regardless of the treatment intervention. Conclusions This study suggests that, in terms of improvement in HRQoL, the heterogenous group of depressive patients in specialized psychiatric care can be successfully treated with behavioral activation in combination with motivational interviewing for those with AUD. ClinicalTrials.gov Identifier NCT02520271 https://clinicaltrials.gov/ct2/show/NCT02520271